The response of different wind-stress forcings on the surges along the east coast of India (MAUSAM, 1981)
Experiments have been performed with a numerical storm surge prediction model (1981) to simulate the surges generated by the 1977 Andhra cyclone by using various formulae representing the wind distribution in the cyclone. It is found that most of these formulations do not give a gold estimate of the observed wind associated with the Andhra cyclone. Accordingly, the computed sea surface elevations along the east coast of India do not agree with the observations. In the present note a new formulation for the computation of the surface winds has been suggested. A comparison of the results by using the well known formulae for the wind distributions has been made.